If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -8x + 3 = c + -3 + 6 Reorder the terms: 3 + 5x + -8x = c + -3 + 6 Combine like terms: 5x + -8x = -3x 3 + -3x = c + -3 + 6 Reorder the terms: 3 + -3x = -3 + 6 + c Combine like terms: -3 + 6 = 3 3 + -3x = 3 + c Add '-3' to each side of the equation. 3 + -3 + -3x = 3 + -3 + c Combine like terms: 3 + -3 = 0 0 + -3x = 3 + -3 + c -3x = 3 + -3 + c Combine like terms: 3 + -3 = 0 -3x = 0 + c -3x = c Solving -3x = c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-3'. x = -0.3333333333c Simplifying x = -0.3333333333c
| u+(-5)=10 | | -8v+6(v+5)=18 | | (1/8)m^3-8n^3=0 | | 8x=8+7x | | 5(x-3)=3(x-4) | | 4*16+8-0/5 | | 300-60+x/2=6x | | 5x^2+6x^2= | | -3x+16=-5 | | y=4x^2-16x | | 10(30)-60+x/2=6x | | 5(p-2)+3(p+1)=25 | | 5-2*(3-6x)=10x | | 4=0.0025p | | -6/7-3/7=4/3u+1/3u | | 5(90-70)=x-126 | | -3(15-3)= | | 2(x+2)-4=30 | | y+(10)=6 | | 1/3y-5/3y=-7/3-1/3 | | -3(x-3)=-36 | | 2w+3=4 | | ln(x-3)=ln(2) | | 3x/2+1=11/2 | | 111-3x=24x+24 | | y=5/2x+6 | | 7x-2x+4-5=3x-1 | | x-60=-17/2(y-20) | | 8p-p+14=1-6p | | 7x+3*(2x-4)=0 | | 2x+3x+7=-43 | | 2(v+8)=9v-47 |